2006
DOI: 10.1016/s0076-6879(06)06001-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biochemical Properties of Rac1, 2, 3 and the Splice Variant Rac1b

Abstract: Rac proteins (Rac1, 1b, 2, 3) belong to the GTP-binding proteins (or GTPases) of the Ras superfamily and thus act as molecular switches cycling between an active GTP-bound and an inactive GDP-bound form through nucleotide exchange and hydrolysis. Like most other GTPases, these proteins adopt different conformations depending on the bound nucleotide, the main differences lying in the conformation of two short and flexible loop structures designated as the switch I and switch II region. The three distinct mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The intermediate efficiency group consists of the Dbl members p190 and p115 (29) as well as the oligo-specific Dbl proteins PRex1, Dbl, and Dbs. We also indexed Tiam1-Rac2 to this group as Tiam1 clearly revealed lower specificity for Rac1 and Rac3, as discussed previously (45,46). The third group with low efficiency is populated not only by Cdc42-specific hPem2/Collybistin and Tuba, Rac-specific TrioN, but also by PRex1, Dbl, Dbs, Vav2, and TrioN with broad specificity.…”
Section: Extent (mentioning
confidence: 62%
“…The intermediate efficiency group consists of the Dbl members p190 and p115 (29) as well as the oligo-specific Dbl proteins PRex1, Dbl, and Dbs. We also indexed Tiam1-Rac2 to this group as Tiam1 clearly revealed lower specificity for Rac1 and Rac3, as discussed previously (45,46). The third group with low efficiency is populated not only by Cdc42-specific hPem2/Collybistin and Tuba, Rac-specific TrioN, but also by PRex1, Dbl, Dbs, Vav2, and TrioN with broad specificity.…”
Section: Extent (mentioning
confidence: 62%
“…Rac1b, an alternative splice variant of Rac1, contains a 19-amino acid insert immediately behind the switch II region (residues 60 -76) of Rac1. This has been shown to be sufficient to disrupt effector interaction itself (19,30,57,58 Previous studies demonstrated that Ras causes activation of Rac and that Rac function is critical for Rasmediated growth transformation. In these studies, Rac function was blocked by use of a dominant negative Rac1(17N) mutant (11,12), which blocks RacGEF activation of Rac (59), or by NSC23766, a cellpermeable small molecule that can bind directly to Rac1 and prevent its activation by Rac-specific RhoGEFs (27).…”
Section: Discussionmentioning
confidence: 99%
“…Rac proteins were prepared similarly as described elsewhere (30,35,36). Briefly, BL21(DE3) cells expressing Rac1, Rac1b, Rac2, and Cdc42, respectively, were incubated at 37°C, before induction with 1 mM isopropyl 1-thio-␤-D-galactopyranoside for 4 h at 37°C (Rac3 required overnight induction at room temperature).…”
Section: Methodsmentioning
confidence: 99%
“…Rac belongs to the superfamily of Ras GTPases, and four isoforms, Rac1, Rac1b, Rac2, and Rac3, have been identified (87). Rac1 is expressed in nonhematopoietic cells and is likely the activator of Nox1, Nox3, Nox4, and Nox5, whereas Rac2 is expressed mostly in hematopoietic cells and is required for the activation of Nox2 in neutrophils (100).…”
Section: Rac1 As a Key Regulator Of Vascular Nadph Oxidasementioning
confidence: 99%